2014
DOI: 10.1682/jrrd.2013.02.0056
|View full text |Cite
|
Sign up to set email alerts
|

User ratings of prosthetic usability and satisfaction in VA study to optimize DEKA Arm

Abstract: Abstract-The Department of Veterans Affairs study to optimize the DEKA Arm provided feedback to inform optimization of the gen 2 (second-generation) prototype and evaluate the gen 3 (third-generation) prototype. This article summarizes recommendations to improve gen 2 and reports satisfaction and usability ratings of gen 2 and gen 3. Data were collected from 39 subjects; 37 subjects were included in this analysis. Of the subjects, 24 were fit with gen 2 (8 radial configuration [RC], 6 humeral configuration [HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
(14 reference statements)
1
20
0
Order By: Relevance
“…The DEKA Arm (both gen 2 and gen 3) is available in three configurations: radial configuration (RC), humeral configuration (HC), and shoulder configuration (SC) (see Figure 1 in Resnik and Borgia in this issue for gen 2 and gen 3 SC prototypes [4]). The SC has 10 powered degrees of freedom and additional passive degrees of freedom [5][6] (Table 1).…”
Section: Deka Armmentioning
confidence: 99%
See 3 more Smart Citations
“…The DEKA Arm (both gen 2 and gen 3) is available in three configurations: radial configuration (RC), humeral configuration (HC), and shoulder configuration (SC) (see Figure 1 in Resnik and Borgia in this issue for gen 2 and gen 3 SC prototypes [4]). The SC has 10 powered degrees of freedom and additional passive degrees of freedom [5][6] (Table 1).…”
Section: Deka Armmentioning
confidence: 99%
“…Three iterations of foot controls (see Figure 2 in Resnik and Borgia in this issue [4]) were used: force sensitive resistors (FSRs); inertial measurement units (IMUs) during gen 2 (IMU-1); and a refined version of the IMU in gen 3 (IMU-2) that did not require an external arm control interface (ACI) unit worn on the ankles and had new features, including the ability to detect walking motion and to automatically put the arm into standby (called Walk Detect).…”
Section: Deka Armmentioning
confidence: 99%
See 2 more Smart Citations
“…A study of user reviews of the Dean Kamen (DEKA) Arm -one of the most advanced prosthetic arms -by the US Department of Veterans Affairs (2014) reported that as many as 30% of the people were dissatisfied, mainly due to issues linked to optimization (Resnik and Matthew 2014). Unlike other electronic gadgets that can be identically mass produced, optimal use of a prosthetic arm is not just about the list of capacities of the device, but is also about how suitable and how safe it is for each user.…”
mentioning
confidence: 99%